Assessment of reservoir sedimentation using remote sensing and recommendations for desilting Patratu Reservoir, India. Issue 4 (11th March 2016) - Pandey, Ashish; Chaube, U.C.; Mishra, S.K.; Kumar, Dheeraj
ABSTRACT: This study describes the assessment of reservoir sedimentation of the Patratu Reservoir using Satellite Remote Sensing (SRS). The sedimentation assessment was carried out using satellite data and reservoir water level data from 2006 to 2012. Water spread area was analysed from satellite data. The Normalized Difference Water Index (NDWI) has been used to delineate open water features and to enhance the presence of water surface in satellite imagery of the Patratu Reservoir. Water spread area of the reservoir at a particular elevation on the date of the passing of the satellite was used to develop an elevation-area curve. For the present case, fluctuation of water level was found to vary from 387.096 to 406.152 m. The linear interpolation/extrapolation technique has been employed to assess the water spread area of Patratu Reservoir at different elevations. Further, these areas were used to compute the live storage capacity of the reservoir between two elevations by the Prismoidal formula. From the study, it was found that due to sedimentation, the live storage capacity of Patratu Reservoir has reduced from 101.95 to 89.96 hm 3, thus showing capacity loss of 11.76% in a span of 44 years. To increase the live storage capacity of the reservoir it is proposed to adopt manual and mechanical digging combined with flushing for desilting of the deposited sediment.EDITOR D. KoutsoyiannisASSOCIATE EDITOR S. Kanae